Efficacy of 2% Lignocaine With Adrenaline Application in Nasal Cavity Before Nasal Surgeries - Maryam, Shanza; Zahid, Bilal; Fayyaz, Ayesha (Biological and Clinical Sciences Research Journal, 2025)
Bleeding that occurs in excess amounts during a nasal surgery can obscure the vision leading to longer hours and increased chances of complications. The application of 2% lignocaine accompanied with adrenaline as a vasoconstrictor is widely adopted in order to reduce bleeding. Objective: This study aimed to evaluate the efficacy of 2% lignocaine with adrenaline in reducing blood loss during the surgery. Methodology: A descriptive case series was conducted at the University of Lahore Teaching Hospital over six months. Seventy-four patients aged 20 to 60 underwent various nasal surgeries, excluding those with specific medical conditions. Procedures were performed under general anesthesia, measuring blood loss and defining efficacy as less than 10mL. Data were analyzed using SPSS version 25.0 with a significance level of p ≤ 0.05. Results: Among the 74 patients, 42 (56.8%) were male and 32 (43.2%) were female. The mean age was 39.23 ± 11.41 years. The mean intra-operative blood loss was 8.40 ± 1.80 mL.Efficacy was observed in 56 patients (75.7%), while 18 patients (24.3%) had blood loss exceeding 10 mL. Conclusion: Applying 2% lignocaine with adrenaline in the nasal cavity before surgery greatly reduces intra-operative blood loss by 75.7%. Larger sample size studies and comparisons with other vasoconstrictors are advised for further investigation.